If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 7) = -4x + 4 Reorder the terms: 4(7 + x) = -4x + 4 (7 * 4 + x * 4) = -4x + 4 (28 + 4x) = -4x + 4 Reorder the terms: 28 + 4x = 4 + -4x Solving 28 + 4x = 4 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 28 + 4x + 4x = 4 + -4x + 4x Combine like terms: 4x + 4x = 8x 28 + 8x = 4 + -4x + 4x Combine like terms: -4x + 4x = 0 28 + 8x = 4 + 0 28 + 8x = 4 Add '-28' to each side of the equation. 28 + -28 + 8x = 4 + -28 Combine like terms: 28 + -28 = 0 0 + 8x = 4 + -28 8x = 4 + -28 Combine like terms: 4 + -28 = -24 8x = -24 Divide each side by '8'. x = -3 Simplifying x = -3
| 3x+(-7)=-25 | | 8y-32=-8(y+6) | | 25x^2-45x+8= | | 5x^2-36x+36= | | 35-19=2(x-8) | | graphy=-2x-4 | | 3x^2/5=27 | | 4k^2-9= | | 1.2y=3+y+1 | | 3y=8+y+1 | | 10x^2-41x-45= | | -9x=6 | | 2v+7-5v=-17 | | 7=-3+9 | | 3y=y+3+1 | | .03(x+40)+12.8=.4(10-x)+96 | | (3x-5)(-5)= | | 27x^2-246x-240= | | 6(5-x)-3(x-4)=6 | | p^2+p-20=0 | | 46-11=5(x-8) | | 6x^2-x+3=0 | | 4x^2-10x+25=49 | | 64-6x=12x+16 | | 10x^2-80x= | | 12-8x=111-29 | | 8w^3-3w+1=0 | | 4(2-3x)-30=10-2(x-4) | | 27x-30x=7-10 | | 9/x=15/35 | | 4v-16=48 | | 14x^2+26x-48= |